2020
DOI: 10.20944/preprints202004.0359.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Diversity and Evolution, Diagnosis, Prevention, and Therapeutics of the Pandemic COVID-19 Disease

Abstract: A novel coronavirus COVID-19 was first emerged in Wuhan city of Hubei Province in China in December 2019. The COVID-19, since then spreads to 213 countries and territories, and has become a pandemic. Genomic analyses have indicated that the virus, popularly named as corona, originated through a natural process and is probably not a purposefully manipulated laboratory construct. However, currently available data are not sufficient to precisely conclude the origin of this fearsome virus. Genome-wide annotation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 99 publications
(225 reference statements)
0
5
0
Order By: Relevance
“…Full-size DOI: 10.7717/peerj.9572/ fig-9 candidates for COVID-19 are now under trials, some of them are advanced to human trials (Lane, 2020), none has yet been declared to be effective and safe for prevention of SARS-CoV-2 infections. Strikingly, no effective therapeutic drugs or vaccines are yet to be available for the treatment of SARS-CoV-2 patients (Hoque et al, 2020a). Through a comprehensive genomic and proteomic study, we endeavor to design an antigenic multiepitope (immunodominant) chimeric vaccine for SARS-CoV-2, named as CoV-RMEN (417 aa), which will nullify the involvement of lab-escape viral transmission, reduce the cost, and may elicit immunity by selectively stimulating antigen-specific B-and T-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-size DOI: 10.7717/peerj.9572/ fig-9 candidates for COVID-19 are now under trials, some of them are advanced to human trials (Lane, 2020), none has yet been declared to be effective and safe for prevention of SARS-CoV-2 infections. Strikingly, no effective therapeutic drugs or vaccines are yet to be available for the treatment of SARS-CoV-2 patients (Hoque et al, 2020a). Through a comprehensive genomic and proteomic study, we endeavor to design an antigenic multiepitope (immunodominant) chimeric vaccine for SARS-CoV-2, named as CoV-RMEN (417 aa), which will nullify the involvement of lab-escape viral transmission, reduce the cost, and may elicit immunity by selectively stimulating antigen-specific B-and T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…This SARS-CoV-2 is the third coronovairus (CoV) belonging to Genus Betacoronavirus that can infect human after the two previously reported coronavirus-severe acute respiratory syndrome (SARS-CoV) (Almofti et al, 2018;Wu et al, 2020), and Middle East respiratory syndrome (MERS-CoV) (Badawi et al, 2016;Pallesen et al, 2017;Ul Qamar et al, 2019). The SARS-CoV-2 has a positive-sense, single-stranded, and ∼30 kilobase long RNA genome showing 79.0% and 50.0% identity to the genomes of SARS-CoV and MERS-CoV, respectively (Abdelmageed et al, 2020;Tang et al, 2020;Lu et al, 2020;Hoque et al, 2020a). Among multiple encoded proteins (structural, non-structural, and accessory), four major structural proteins are the spike (S) glycoprotein, small envelope protein (E), membrane protein (M), and nucleocapsid protein (N) (Ahmed, Quadeer & McKay, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first reported case of 'pneumonia' in Wuhan city of Hubei Province in China in December 2019 [1], it took only a couple of months before the novel coronavirus disease (COVID- 19) was declared a pandemic by the World Health Organization (WHO) [2]. The causative virus, Severe Acute Respiratory Coronavirus-2 (SARS-CoV-2) or nCoV-19, is the seventh coronavirus known to infect humans [3] . Andersen et al (2020) suggested that the virus might use an intermediary host (Malayan pangolins) of high population density after jumping from the reservoir bat (Rhinolophus affinis ) for acquiring the optimized SARS-CoV-2 RBD (Receptor-binding domain) region and polybasic cleavage sites through the natural selection process, or the selection process could occur in humans following the zoonotic transfer [4].…”
Section: Introductionmentioning
confidence: 99%
“…What makes the virus deadly is the ability to transmit from human to human through casual contact by droplet, fomite, and direct contact routes, whereas recent studies have also indicated possible airborne, fecal, and intrauterine transmission leading to an increase in the cases worldwide with no direct treatment available yet where many researches are going on [6]. As of 10 th May 2020, 3.99 million COVID-19 cases have been confirmed in more than 213 countries and territories, with 2,78,941 deaths [3,[7][8][9]. At the initial stage, China was the epicenter which was changed to Italy, UK, and later to the USA while the South Asian and African countries came later in the epidemic timeline [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The genome of SARS-CoV-2 virus encodes for four major structural proteins such as the spike (S) protein, nucleocapsid (N) protein, membrane (M) protein, and the small envelope (E) protein, all of which are required to complete a successful infectious event/replication cycle of virus including entry, assembly, packaging and release of new virus particles within the human cells [8][9][10][11] . The E protein is the smallest of the major structural proteins, and associated with viral assembly, budding, envelope formation, and pathogenesis 7 . During the replication cycle, the virus expresses the E protein in high abundance inside the host cell, however, only a small portion is incorporated into the virion envelope.…”
mentioning
confidence: 99%